1997
DOI: 10.1136/gut.40.5.608
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal tolerability of nitroxybutyl-flurbiprofen in rats.

Abstract: Background-Nitric oxide derivatives of non-steroidal anti-inflammatory drugs (NSAIDs) are thought to be much less ulcerogenic than their parent compounds. Aim-To compare the effect and potency of flurbiprofen and nitroxybutyl-flurbiprofen to uncouple mitochondrial oxidative phosphorylation (an early pathogenic event in NSAID enteropathy), increase intestinal permeability (transitional stage), and cause macroscopic small intestinal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…This study used higher drug doses and a much stricter dosing regime (twice daily dosing for over 2 weeks compared to our single dose over 8 days). However, Somasundaram (1997) using nitroxybutyl-fl urbiprtofen obtained almost identical results to the current study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study used higher drug doses and a much stricter dosing regime (twice daily dosing for over 2 weeks compared to our single dose over 8 days). However, Somasundaram (1997) using nitroxybutyl-fl urbiprtofen obtained almost identical results to the current study.…”
Section: Discussionsupporting
confidence: 90%
“…This raises the possibility that the benefi cial action of AZD3582 on the stomach WilderSmith et al, 2006) may simply be due to its lack of topical toxicity (Rainsford and Whitehouse, 1980). While both drugs were associated with similar increases in intestinal permeability there were no infl ammatory changes following the lower (10 or 30 µmol/kg) doses of the drugs unlike previous studies where infl ammation invariably follows the intestinal permeability changes (Somasundaram et al, 1997;Somasundaram et al, 2000). The reasons for this may be that much higher doses of NSAIDs were administered in previous studies.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…It is, however, also clear from Table 1 that it was still possible to detect an ultrastructural effect of indomethacin at all concentrations of the drug in vitro. This is in accordance with in vivo studies that have shown ultrastructural damage to intestinal mitochondria from rats after the animals had been dosed orally with indomethacin [8] and other acidic NSAIDs such as flurbiprofen [16].…”
Section: Discussionsupporting
confidence: 84%
“…Intestinal permeability is thought to be the central and essential mechanism of translating the biochemical/cellular events of NSAIDs to a tissue reaction in the small bowel. 20,[22][23][24][25][26] The purpose of this review is to summarize the studies that underlie our current understanding of NSAIDinduced damage to the small bowel, with a special emphasis on the studies that relate to increased intestinal permeability.…”
Section: Overview and Aimsmentioning
confidence: 99%